Needs Analysis of Student Perception Scale Instruments on Chemical Learning Difficulties - Sabrina Yulia; Sukisman Purtadi (Indonesian Journal of Chemical Education, 2024)
The learning process is the mental activity of individuals in communicating with their environment which is invisible but can be proven through behavioral transformation in a positive direction. In reality, there are several difficulties faced by students such as students who have undergone a deep learning process but still have difficulty achieving learning achievements at school. Learning difficulties experienced by students must be diagnosed by the teacher which aims to determine the situation of student learning difficulties. However, there are obstacles in the unavailability of complete instruments to measure student learning difficulties and teachers have a lack of understanding of the use of measurement instruments. The questionnaire instrument will help teachers in diagnosing students' learning difficulties. Before its development, a needs analysis stage is needed to adjust the characteristics of the instrument design according to the data in the field. The needs analysis using a questionnaire consists of 3 aspects (17 questions) with 7 chemistry teacher participants in Yogyakarta. The needs analysis questionnaire has been validated by chemistry learning experts. The results of the data were analyzed using descriptive qualitative by presenting data or answers calculating frequencies and percentages. It was concluded that the development of a student perception scale instrument on chemistry learning difficulties has an urgency that is quite important because of the limitations or unavailability of these measurement instruments.